METAKOGNISI DAN PENYESUAIAN DIRI SISWA AKSELERASI - Ribka Dwi Sulistyorini; Agustin Rahmawati (University of Merdeka Malang, 2013)
Metacognition is the ability to regulate and control the thought process. With this ability a person capable of controlling the thought processes going on yourself. Thought to be the basis of an individual to behave. By having a good metacognitive skills then the individual will be able to adjust themselves well with their social environment. This is quite important for each individual, especially for students who have the acceleration constraints in terms of adjustment. Students acceleration has tremendous potential and would be very unfortunate if potential students have hampered the acceleration due to adjustment problems with the surrounding environment. By having a good metacognition acceleration then students can control his thoughts and also can control every thing was going to do, including in terms of adjusting to. The population in this study were senior high school students are accelerated in the city of Malang as many as 177 students. The sample in this study is the accelerated student who was in class XI as many as 94 students. That used research bottom is the Purposive Sampling. The process of data analysis used were asumption test, both are normality testing and linierity testing. From linierity testing were found result linier line with equation Y = 1,29 + 0,52X, which indicates that there is a positive relationship between metacognition with self-adjustment, so that the working hypothesis (Ha) which states there is a connection with the adjustment received metacognition .